Pengembangan E-Learning Materi Usaha Dan Pesawat Sederhana Untuk Meningkatkan Keterampilan Berfikir Kreatif Siswa SMP - Hersi Sativa; Ketang Wiyono; Leni Marlina (Jurnal Ilmu Fisika dan Pembelajarannya (JIFP), 2022)
Physics learning has a purpose to improve students' thinking skills so that not only competent in the psychomotor and cognitive fields, but should support the way students think creatively, students think systematically, and also students think logicall. Therefore this research aims to develop e-learning on work and simple machines to improve creative thinking skills of grade VIII students SMPIT Harapan Mulia Palembang. The research uses development research methods, with development models Alessi and Trollip. The development of Alessi and Trollip models has three stages of planning, design, and development. The data collected in the study used several techniques including using expert validation sheets, student response questionnaires and interviews. The results of the research concluded that e-learning on work and simple machines for grade VIII middle school students has been feasible, practical and can improve students’ creative thinking skills.